Rethinking humanitarian action: In the age of intelligence, we can do even more with less - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Humanitarian funding dropped by 39% this year. Yet needs have never been higher. What if there were a smarter, more efficient way to respond?